Analytical expressions for the FM and AM responses of an integrated laser-modulator - Brosson, Philippe; Bissessur, Hans (Institute of Electrical and Electronics Engineers (IEEE), 1996)
The need for low-chirp and compact transmitters for high-bit-rate optical links has led to the development of integrated laser electroabsorption modulators (ILM). We have investigated feedback effects inducing frequency chirp by developing a model treating the ILM as a whole and obtained analytical expressions of the FM and AM responses. The variation of the frequency chirp with the residual facet reflectivity of the modulator section is calculated. The model predicts the unusual peak in the measured frequency responses and has been used to define design rules.
Keywords: Diffraction gratings; Distributed feedback lasers; Electric currents; Frequency response; Light absorption; Light modulators; Light propagation; Mathematical models; Optical fiber coupling; Optical links; Refractive index; Bragg propagation constant; Current intensity; Frequency chirp; Grating coupling coefficient; Integrated laser modulator; Integrated optoelectronics